Renal cell carcinoma and malignant peritoneal mesothelioma after occupational asbestos exposure: case report - Candura, Stefano Massimo; Boeri, Riccardo; Teragni, Cristina; Chen, Yao; Scafa, Fabrizio (La Medicina del Lavoro, 2016)
Asbestos is the main causal factor for malignant mesothelioma (MM), a relatively rare and aggressive malignancy. Some epidemiological evidence suggests a role of this agent also in the etiology of renal cell carcinoma (RCC), the most common form of kidney cancer. Case report: After 7 years of asbestos exposure, a 76-year-old asbestos-cement worker came to our notice with left flank pain. Diagnostic imaging disclosed a neoplasm in the upper two thirds of the left kidney, without evidence of metastases. After surgery (nephrectomy with para-aortic lymphadenectomy), histopathology revealed clear cell RCC. One year later, the patient was hospitalized for abdominal pain. Laparoscopy showed diffuse neoplastic infiltration of the peritoneum and liver. Histological and immunohistochemical examination of the bioptic samples led to the diagnosis of biphasic MM. The subject died 2 months later. Autopsy disclosed ascites and diffuse infiltration of the abdominal wall and viscera, without evidence of RCC relapse. Conclusions: This is the second reported case of association between RCC and peritoneal MM in the scientific literature. Asbestos might be involved in the causation of both malignancies.